Introducing the Nepal Journal of Epidemiology: A Pioneer in its Domain - Sathian, Brijesh (Nepal Journal of Epidemiology, 2010)
The Nepal Journal of Epidemiology is the first journal of its kind in Nepal. Our main objective in pioneering this journal is to attempt to provide a common platform for all researchers, particularly those doing epidemiological studies on prevailing public health problems in the community. DOI: 10.3126/nje.v1i1.4099 Nepal Journal of Epidemiology 2010;1 (1):1-3